Precursors of thymic peptides as stress sensors. (1st December 2020) - Lunin, Sergey; Khrenov, Maxim; Glushkova, Olga; Parfenyuk, Svetlana; Novoselova, Tatyana; Novoselova, E
ABSTRACT: Introduction: A large volume of data indicates that the known thymic hormones, thymulin, thymopoietin, thymosin-α, thymosin-β, and thymic humoral factor-y2, exhibit different spectra of activities. Although large in volume, available data are rather fragmented, resulting in a lack of understanding of the role played by thymic hormones in immune homeostasis. Area covered: Existing data compartmentalizes the effect of thymic peptides into 2 categories: influence on immune cells and interconnection with neuroendocrine systems. The current study draws attention to a third aspect of the thymic peptide effect that has not been clarified yet, wherein ubiquitous and highly abundant intranuclear precursors of so called 'thymic peptides' play a fundamental role in all somatic cells. Expert opinion: Our analysis indicated that, under certain stress-related conditions, these precursors are cleaved to form immunologically active peptides that rapidly leave the nucleus and intracellular spaces, to send 'distress signals' to the immune system, thereby acting as stress sensors. We propose that these peptides may form a link between somatic cells and immune as well as neuroendocrine systems. This model may provide a better understanding of the mechanisms underlying immune homeostasis, leading thereby to the development of new therapeutic regimes utilizing the characteristics of thymic peptides.